Differential Response of Oral Mucosal and Gingival Cells to Corynebacterium durum, Streptococcus sanguinis, and Porphyromonas gingivalis Multispecies Biofilms - Redanz, Ulrike; Redanz, Sylvio; Treerat, Puthalayai; Prakasam, Sivaraman; Lin, Li-Jung; Merritt, Justin; Kreth, Jens (Frontiers in Cellular and Infection Microbiology, 2021)
Polymicrobial interactions with oral mucosal surfaces determine the health status of the host. While a homeostatic balance provides protection from oral disease, a dysbiotic polymicrobial community promotes tissue destruction and chronic oral diseases. How polymicrobial communities transition from a homeostatic to a dysbiotic state is an understudied process. Thus, we were interested to investigate this ecological transition by focusing on biofilm communities containing high abundance commensal species and low abundance pathobionts to characterize the host-microbiome interactions occurring during oral health. To this end, a multispecies biofilm model was examined using the commensal species Corynebacterium durum and Streptococcus sanguinis and the pathobiont Porphyromonas gingivalis. We compared how both single and multispecies biofilms interact with different oral mucosal and gingival cell types, including the well-studied oral keratinocyte cell lines OKF4/TERT-1and hTERT TIGKs as well as human primary periodontal ligament cells. While single species biofilms of C. durum, S. sanguinis, and P. gingivalis are all characterized by unique cytokine responses for each species, multispecies biofilms elicited a response resembling S. sanguinis single species biofilms. One notable exception is the influence of P. gingivalis upon TNF-α and Gro-α production in hTERT TIGKs cells, which was not affected by the presence of other species. This study is also the first to examine the host response to C. durum. Interestingly, C. durum yielded no notable inflammatory responses from any of the tested host cells, suggesting it functions as a true commensal species. Conversely, S. sanguinis was able to induce expression and secretion of the proinflammatory cytokines IL-6 and IL-8, demonstrating a much greater inflammatory potential, despite being health associated. Our study also demonstrates the variability of host cell responses between different cell lines, highlighting the importance of developing relevant in vitro models to study oral microbiome-host interactions.